2006
DOI: 10.1002/pssc.200669590
|View full text |Cite
|
Sign up to set email alerts
|

Optical and electrical properties of phosphorus‐doped ZnMgTe bulk crystals grown by Bridgman method

Abstract: Phosphorus‐doped Zn1–x Mgx Te crystals with Mg concentration x of 0 to 0.33 have been grown by vertical Bridgman method. The lattice constant, transmissivity and band‐gap energy as a function of x have been determined. The linear relation has been found between the lattice constant or band‐gap energy and x . The number of precipitates in Zn1–x Mgx Te single crystals seems to be less than that in ZnTe grown from VGF method. The p ‐type Zn1–x Mgx Te (x ≤ 0.19) crystals with carrier concentration of ∼1017 cm–3 we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
11
0

Year Published

2010
2010
2012
2012

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 12 publications
1
11
0
Order By: Relevance
“…It was confirmed that the relationship between x and the peak energy of RT emission band is consistent with x dependent band gap obtained using RT cathodoluminescence measurement [5]. Figure 4 shows the temperature dependent peak energy of A-band.…”
Section: Contributedsupporting
confidence: 85%
See 2 more Smart Citations
“…It was confirmed that the relationship between x and the peak energy of RT emission band is consistent with x dependent band gap obtained using RT cathodoluminescence measurement [5]. Figure 4 shows the temperature dependent peak energy of A-band.…”
Section: Contributedsupporting
confidence: 85%
“…There are only a few works on P-doped Zn 1-x Mg x Te bulk crystals [3][4][5] that are very important for fabricating ZnTe based LED. So far, we have prepared P-doped Zn 1-x Mg x Te crystals by means of Bridgman method and also clarified the fundamental properties such as Mg composition (x), optical and electrical properties, lattice constant, and so on [4,5]. Very recently, we have successfully prepared the high crystalline quality of P-doped Zn 1-x Mg x Te crystal for ZnTe based LED [6].…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…With respect to bulk growth of Zn 1 À x Mg x Te crystals, several investigations have so far been carried out mainly using the Bridgman technique [1,2,[4][5][6][7][8][9], which is simple and leads to low cost. However, there are only a few works on phosphorus (P)-doped Zn 1 À x Mg x Te bulk crystals [4,6] except for our previous studies [2,8,9].…”
Section: Introductionmentioning
confidence: 99%
“…Zn 1 À x Mg x Te ternary alloy is a promising material for light emitting diodes (LEDs) with green or blue emission since the fundamental energy gap of Zn 1 À x Mg x Te can be varied through Mg composition from 2.26 to 3.1 eV [1] or 3.2 eV [2]. Furthermore, Zn 1 À x Mg x Te is expected to be one of the best materials as a cladding layer and a transparent substrate for improving the performance of ZnTe-based pure green LED because it is expected to form a type-I heterostructure with ZnTe [3].…”
Section: Introductionmentioning
confidence: 99%